CODE-SWITCHING IN SECOND LANGUAGE ACQUISITION: A STUDY OF INTERNATIONAL STUDENTS IN PALEMBANG - Siriabbangan, Agnes Aristi; Aprilia, Fitria; Neisya, Neisya (Jurnal Ilmiah Bina Bahasa, 2025)
This research investigates the use of code-switching as a linguistic and sociocultural strategy among international students in Palembang. While code-switching has been extensively examined, its use as a tool for academic and social adaptation among international students in Indonesian higher education is still limited. Addressing this gap, the study aims to explore the types of code-switching employed and to examine how social and academic factors shape students’ language-switching behaviors within the framework of second language acquisition. Adopting a qualitative case study method, data were collected through semi-structured interviews, observations, and recorded conversations with international students from Mali and Egypt. It showed that the participants utilized all three forms of code-switching—tag switching, inter-sentential switching, and intra-sentential switching—with inter-sentential switching being the most frequent. Code-switching served to navigate lexical gaps, clarify meaning, strengthen social bonds, and express personal identity. Social interactions and cultural adaptation emerged as key influences, while academic settings required flexible language use to support learning and participation. The study concludes that code-switching is not a linguistic deficiency but a strategic and adaptive resource that facilitates language development, social integration, and academic engagement. These insights may create inclusive and supportive learning environments for international students in multilingual educational contexts.